Among the Brave - Haddix, Margaret Peterson (New York Scholastic, 2004)
In a society that allows families to have only two children, a group of third-borns tries to save themselves and others like them. Fifth in the series.
"A Shadow Children book."
"This edition is only available for distribution through the school market"--P. [4] of cover.
Originally published: New York : Simon & Schuster Books for Young Readers, c2004.
88691
Keywords: Social control -- Juvenile fiction; Self-preservation -- Juvenile fiction; Survival -- Fiction; Science fiction